Strategi pembelajaran bahasa arab yang menyenangkan dan interaktif di Madrasah Ibtidaiyah - Nurkarimah, Ika (Maliki Interdisciplinary Journal, 2025)
Arabic is an important international language to learn, but learners often face challenges in constructing sentences, especially beginners. The Arabic language learning in Madrasah Ibtidaiyah (MI) aims to enhance students' communication skills and provide religious understanding from an early age. However, the dominance of traditional methods has led to a decline in student interest. This research aims to design an interactive and enjoyable Arabic language learning approach, such as language games, audio-visual media, and project-based learning. This approach is expected to improve students' understanding and create a positive learning environment. Language games help students master language skills in a fun way, while audio-visual media, such as animated videos and songs, can clarify the material and increase student interest. Project-based learning allows students to apply Arabic knowledge in more real-world contexts, such as creating posters or writing stories. The research results show that the use of this approach significantly enhances students' motivation and language skills, creates a more engaging learning experience, and supports the achievement of learning objectives at MI. This approach can also foster a generation of students with a strong and creative understanding of the Arabic language.